Encyclopedia of Inorganic and Bioinorganic Chemistry 2014
DOI: 10.1002/9781119951438.eibc2026
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide Amides

Abstract: Lanthanides form a wide (and increasing) variety of alkyl‐ and arylamides. Most are in the (+3) oxidation state, but simple alkylamides of Sm( II ), Eu( II ), Yb( II ), and Ce( IV ) are known. The largest and best characterized group are three coordinate tris(bis(trimethylsilyl)amide) compounds, [Ln(N( SiMe 3 ) 2 ) 3 ], which have un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
1
2
0
Order By: Relevance
“…A Raman signature at 1950 cm –1 is also observed to increase with the addition of the U­(III)/mixed FP surrogate sample (Figure B) and is hypothesized to be a fluorescence signature of one of the lanthanides present. While this will be explored further under future work, the hypothesis aligns with the known data that several lanthanides exhibit fluorescence in other media. , …”
Section: Resultssupporting
confidence: 65%
“…A Raman signature at 1950 cm –1 is also observed to increase with the addition of the U­(III)/mixed FP surrogate sample (Figure B) and is hypothesized to be a fluorescence signature of one of the lanthanides present. While this will be explored further under future work, the hypothesis aligns with the known data that several lanthanides exhibit fluorescence in other media. , …”
Section: Resultssupporting
confidence: 65%
“…Tris­[ N , N -bis­(trimethylsilyl)­amido]­lanthanide complexes (Ln­[N­(SiMe 3 ) 2 ] 3 , abbreviated here as Ln NTMS ) are encountered frequently in the lanthanide catalysis literature, both as precursors to more complex lanthanide organometallics and as homogeneous catalysts, particularly for hydro-functionalization/reduction of alkenes and alkynes. These complexes are commercially available for many lanthanides, or can be readily synthesized and purified, rendering them highly accessible and of great interest to the synthetic methods community. A report from the Marks laboratory showed that it is possible to carry out the catalytic synthesis of amides with Ln NTMS , but the La NTMS -catalyzed reduction of amides had not yet been investigated. Given this, and the proven ability of La NTMS to catalyze carbonyl hydroboration, La NTMS -catalyzed amide hydroboration was an intriguing target.…”
Section: Introductionmentioning
confidence: 99%
“…Tris­[ N , N -bis­(trimethylsilyl)­amido]­lanthanide complexes (Ln­[N­(SiMe 3 ) 2 ] 3 , abbreviated here as Ln NTMS , Figure B) are commercially available for many lanthanides, or they can be readily synthesized/purified, rendering them accessible and of great utility to the synthetic method community . As such, they are frequently employed as precursors to more elaborate lanthanide organometallics and as homogeneous catalysts, particularly for alkene/alkyne hydrofunctionalization . Recently, we reported that La NTMS displays remarkable catalytic activity for ketone and aldehyde hydroboration with HBpin (Figure B), with turnover frequencies as high as 40 000 h –1 at 25 °C .…”
Section: Introductionmentioning
confidence: 99%